2002
DOI: 10.1111/1471-8847.00034
|View full text |Cite
|
Sign up to set email alerts
|

End of Life in HIV‐infected Children Who Died in Hospital

Abstract: The aim of this study was to evaluate terminal care among hospitalized children who died of HIV/AIDS. The design was a retrospective chart review of the terminal hospitalization. The setting was a public, secondary and tertiary children's hospital in Cape Town, South Africa (SA). The patients included a consecutive series of in-patient deaths from HIV-related causes. The main outcome measures included: documentation of do not resuscitate (DNR) orders and comfort care plans, intensity of diagnostic and therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Optimal terminal HIV/AIDS care requires a primary focus on palliation, and palliation requires clear and precise terminology to avoid the inconsistency found in clinical instruction for HIV/AIDS terminal care. 41 The heterogeneous clinical studies included in this review reflect the diverse settings, clinical management strategies, and disease stages relevant to palliative care in HIV disease. A lack of detailed service description for many of the studies meant it was not possible to identify the effective elements of the service that might be replicated, although exceptions were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal terminal HIV/AIDS care requires a primary focus on palliation, and palliation requires clear and precise terminology to avoid the inconsistency found in clinical instruction for HIV/AIDS terminal care. 41 The heterogeneous clinical studies included in this review reflect the diverse settings, clinical management strategies, and disease stages relevant to palliative care in HIV disease. A lack of detailed service description for many of the studies meant it was not possible to identify the effective elements of the service that might be replicated, although exceptions were found.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to minimise the bias resulting from terminology by including a broad range of common terms in the search strategy-for example, palliative care approaches being termed comfort care. 41 This review also was guided by the findings from a recent evaluation of systematic reviews of palliative care services. 47 Similarly, the grading criteria selected were purposefully broad and inclusive, allowing a full body of evidence rather than being narrow (and RCT focused).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most common causes of distress during the last 48 hours of life are respiratory distress (49%), oral and esophageal candidiasis (37%) and painful skin conditions (32%). 89 Uganda is the first and only African country where palliative home-based care (including provision of free morphine) is part of the national health program. 90 There has been little research into psychosocial support for African HIV-infected children and their families.…”
Section: Emotional Support Pain Relief and Palliative Carementioning
confidence: 99%
“…The large numbers of HIV-infected patients and the lack of available resources for their care when they develop secondary complications, could contribute to patients dying much sooner than patients in developed countries. This speculation is substantiated by a study conducted in respect of bed charts of South African hospitalised paediatric HIV/AIDS patients, in which it was found that instructions not to resuscitate (DNR) appeared on 84% of the bed charts (Henley, 2002).…”
Section: Discussionmentioning
confidence: 98%